1994
DOI: 10.2337/diab.43.10.1248
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure in the Transition from Normo- to Microalbuminuria: A Longitudinal Study in IDDM Patients

Abstract: To describe the development in blood pressure (BP) in relation to urinary albumin excretion (UAE) more exactly, 44 initially normoalbuminuric type I diabetic patients and 21 healthy individuals were included in a 3.1-year follow-up study by using ambulatory BP (AMBP) monitoring. Six patients developed microalbuminuria according to accepted criteria (progressors; UAE at follow-up was > 20 micrograms/min). Initial UAE was higher in this group (9.0 x/divided by 1.4 micrograms/min) compared with both the nonprogre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
3
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(86 citation statements)
references
References 26 publications
6
76
3
1
Order By: Relevance
“…It has also been observed that an increase in AER values in Type 1 diabetic subjects may be heralded by an abnormal pattern of night-time blood pressure [39]. We cannot, therefore, rule out that differences in blood pressure at baseline may not have been detectable with a single office measurement, but could have been found if 24-h blood pressure measurements had been performed [40,41]. However, at follow-up, systolic blood pressure and the use of anti-hypertension medications were higher in patients who had progressed to macroalbuminuria.…”
Section: Discussionmentioning
confidence: 92%
“…It has also been observed that an increase in AER values in Type 1 diabetic subjects may be heralded by an abnormal pattern of night-time blood pressure [39]. We cannot, therefore, rule out that differences in blood pressure at baseline may not have been detectable with a single office measurement, but could have been found if 24-h blood pressure measurements had been performed [40,41]. However, at follow-up, systolic blood pressure and the use of anti-hypertension medications were higher in patients who had progressed to macroalbuminuria.…”
Section: Discussionmentioning
confidence: 92%
“…In all but one study no difference in BP was observed between healthy controls and patients with normoalbuminuric type 1 diabetes, when adjusting for albuminuria, diabetes duration, age and gender. 3,4,11,12,14,16,[25][26][27] We have used an automatic auscultatory device (Profilomat ® ) to measure 24-h BPs and found no significant difference in 'daytime' or 'night-time' BP or in systolic or diastolic day-night differences between diabetic patients and controls. These results are somewhat in contrast with data from studies in which 24-h BPs were measured with an oscillometric device.…”
Section: Discussionmentioning
confidence: 99%
“…11 Although most cross-sectional as well as longitudinal studies on the prevalence of elevated BP in type 1 diabetes suggest an association between microalbuminuria and BP rise, it is still controversial whether the increase of arterial BP precedes, follows or develops in parallel with the onset of microalbuminuria. [2][3][4][5][6][13][14][15][16]23,24 These discrepancies on the prevalence of increased BP in type 1 diabetic patients at the onset of microalbuminuria can be attributed, at least partially, to differences in the study populations with respect to factors as age, diabetes duration, gender, sodiumintake, presence of autonomic neuropathy, the number of smokers vs non-smokers and urinary albumin excretion. However, from our data it is evident that differences in techniques of BP measurements should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations